2013
DOI: 10.1002/adma.201303060
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Carrier Distribution in Top‐Gate Polymer Field‐Effect Transistors: Correlation between Width of Density of Localized States and Urbach Energy

Abstract: A general semiconductor‐independent two‐dimensional character of the carrier distribution in top‐gate polymer field‐effect transistors is revealed by analysing temperature‐dependent transfer characteristics and the sub‐bandgap absorption tails of the polymer semiconductors. A correlation between the extracted width of the density of states and the Urbach energy is presented, corroborating the 2D accumulation layer and demonstrating an intricate connection between optical measurements concerning disorder and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
181
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 157 publications
(194 citation statements)
references
References 23 publications
9
181
0
Order By: Relevance
“…To verify the presence of CuO on the surface of Cu 2 O, absorption spectra of the etched and unetched thermally oxidized Cu 2 O substrates were taken with photothermal deflection spectroscopy (PDS) -a highly sensitive technique which allows for sub-band gap absorption measurement 24 ( Figure 4). Both spectra showed absorption above 1.4 eV, which coincides with the band gap of CuO, before saturating at 2 eV (Cu 2 O band gap).…”
Section: Representative Resultsmentioning
confidence: 99%
“…To verify the presence of CuO on the surface of Cu 2 O, absorption spectra of the etched and unetched thermally oxidized Cu 2 O substrates were taken with photothermal deflection spectroscopy (PDS) -a highly sensitive technique which allows for sub-band gap absorption measurement 24 ( Figure 4). Both spectra showed absorption above 1.4 eV, which coincides with the band gap of CuO, before saturating at 2 eV (Cu 2 O band gap).…”
Section: Representative Resultsmentioning
confidence: 99%
“…As mentioned earlier, in previously published numerical investigations of OFETs a Gaussian distribution was assumed for the DOS [12,13]. Although this assumption might be correct for ODSCs in general, it is not commonly used for analyzing experimental investigations of OFETs [14][15][16]19]. In fact we found that regardless of the value for the width of the DOS, a Gaussian distribution leads to a near-constant mobility over the whole field range and, in fact, slightly decreases with increasing gate field.…”
Section: Simulationsmentioning
confidence: 86%
“…In the linear transport regime the exponents follow to γ 2D = T 0 /T and γ 3D = 2T 0 /T − 1, respectively, where T is the lattice temperature [15]. In the saturation regime the corresponding exponents follow to γ 2D = T 0 /T + 1 and γ 3D = 2T 0 /T for 2D and 3D transports, respectively [16]. The procedure to obtain the dimensionality of a system can, in short, be described as follows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations